Border Temporalities of an Old Letter. A Hermeneutic Interpretation of Cross-Border Veteran Welfare - Venken, Machteld (Borders in Globalization Review, 2024)
Abstract: „The article uses the concept of border temporalities to offer a hermeneutic interpretation of an old letter containing a request from a cross-border female migrant from Luxembourg to access French welfare benefits. In doing so, it systematically unravels the way in which time was lived and experienced differently by borderland residents as opposed to French lawmakers. The alternative temporality characterizing the third space of the Luxembourgian–German– French borderlands clashed with the spatio-temporal hierarchy imposed by France in the period after the First World War to exclude the majority of people living abroad from access to social provision. The article concludes its hermeneutic circle with a reflection on how historical research on borders and borderlands is conditioned by the temporality of archives and the temporality of research funding.“
Keywords: Archiv; Frau; Fremdheit; Geschichtsschreibung; Grenzgebiet; Hermeneutik; Veteran

Overlapping borders. Images of East Belgium as a transcultural area in contemporary East Belgian literature - Beck, Philippe; Penné, Lesley (Oxford German Studies, 2019)
„In this contribution, we discuss how the East Belgian authors Hannes Anderer, Freddy Derwahl and Leo Wintgens represent history, borders and multilingualism in their novels. These contemporary authors have understood that coming to terms with the past is an important aspect in developing a genuine East Belgian collective identity. Furthermore, the multiple borders (with Germany, the Netherlands and Luxembourg) and the co-existence of several languages in this region have become constitutive of collective self-understanding, also with regard to the construction of a region-specific cultural memory. Finally, we show the narrative strategies used in the novels Unterwegs zu Melusine (2006), Bosch in Belgien (2006) and Wege aus Sümpfen. Roman einer Grenzlandschaft Teil I (2001) and Teil II (2006) in order to bring to bear the relation between minority and majority culture by recurring to imagology.“
Keywords: Annexion; Geschichtsbild; Geschichtsschreibung; Kulturelle Identität; Mehrsprachigkeit; Schriftsteller; Staatsgrenze

Ein Schattendasein in der Geschichtsschreibung. Wenige Blicke auf die Zwischenräume im langen 19. Jahrhundert - Brüll, Christoph; Lejeune, Carlo; Lejeune, Carlo (Code civil, beschleunigte Moderne und Dynamiken des Beharrens (1794–1919), 2017)
Keywords: Geschichtsbild; Geschichtsschreibung; Ostbelgien